Aplikasi Verifikasi Wajah untuk Absensi pada Platform Android dengan Menggunakan Algoritma Fisherface - Wardana, I Putu Putrayana; Giriantari, IA Dwi; Sudarma, Made (Majalah Ilmiah Teknologi Elektro, 2016)
The face is one part of the human body which are often used in biometric recognition system for high-level differences between the faces of the other faces. Android mobile application with additional security face recognition feature will add to the security of personal privacy of a person's use of telephone / mobile in particular that based on android. Extraction is one of the characteristics of the stages through which the development of biometric facial recognition systems on attendance face recognition applications. This stage aims to extract information from the face image so that it can be used as the unique features of the face in question. In this paper face recognition feature extraction phase is done by using algorithms Fisherface. The image of the face through the training process to the alignment faces and extraction fisherface which is then matched by comparing the value euclidiannya. The trial results in this study resulted in fisherface algorithm does not affect the change in facial expression, distance and lighting after testing two hundred thirty facial image database will still be able to recognize a person's face.
Keywords: Aplikasi absensi mobile android face recognition fisherface